Cannabis Use, Use Motives and Cannabis Use Disorder Among Berlin College Students - Naegele, Helene Blanche (Journal of drug issues, 2022)
This study described cannabis use behavior among college students in Berlin, in particular, differences in use motives between subjects with frequent use and those with signs of cannabis use disorder (CUD). Cross-sectional data were collected via an online survey among Berlin college students (N=9350; 50.7% women; Mage=24.4). Motivation scales were computed based on an exploratory factor analysis. Effects of these motive scales were compared using multivariate regression models, where the dependent variable was use intensity (ordinal), frequent use (twice or more per week, binary) or a positive substance use disorder screening test (binary). Cannabis use is known to be particularly prevalent among Berlin college students, which was confirmed by our data. The most frequent use motive was enhancement, which, however, was not associated with frequent use or CUD. The motives predicting frequent use (sociability) are different from motives predicting CUD (coping), even when controlling for a wide array of covariates.